PENERAPAN FUZZY MULTIPLE ATTRIBUTE DECISION MAKING DALAM PEMILIHAN TEMPAT INDEKOS - WIJAYA, I NYOMAN DICKY; GANDHIADI, G.K.; HARINI, LUH PUTU IDA (E-Jurnal Matematika; Vol 11 No 1 (2022), 2022)
Boarding house is an alternative choice for students to fulfill their need for a place to live. The variety of boarding houses, along with their respective advantages and disadvantages, becomes a challenge for students in determining the boarding house that suits their desires and needs. An in-depth evaluation is needed by comparing boarding houses based on certain criteria. In this study will be known the best boarding house based on four assessment criteria, price, facility, location, and room area. This research was conducted in Mathematics Department, Udayana University, using the combination of Fuzzy Analytic Hierarchy Process (FAHP) and Simple Additive Weighting (SAW) method . Sample in this study amounted to 118 respondents, with purposive sampling was the sampling technique. FAHP method is used to obtain the weight of each criterion, with the use of triangular fuzzy numbers for pairwise comparison scale of FAHP, and the use of the extent analysis method for the synthetic extent value  of the pairwise comparison. SAW method is used for the ranking process of 75 boarding houses alternative. The result showed that the weight of each criterion being 32% (price), 23% (facility), 40% (location), and 5% (room area), obtained A46 as the best boarding houses with a percentage gain value of 71%.